A Conceptual Model to Achieve Operational Excellence in a Public Sector Bus Transport Company: A Research Paper - Vetrivel Sezhian, M.; Muralidharan, C.; Deshmukh, S. G. (Prabandhan: Indian Journal of Management, 2012)
This model aims at using the QFD methodology for converting the customer requirements and needs into quality characteristics for improving the quality of service in a public sector passenger transport company, which is a crucial sector for transportation of people in developing countries like India. In this model, traditional quality function deployment has been modified by seamlessly integrating the Principal Component Analysis (PCA) to find the weights for the customer needs and Conjoint Analysis (CA) to aid the prioritization of the technical descriptors. This QFD would help to prioritize the different technical measures to focus and improve to achieve operational excellence.